Analisis Penyebab Penurunan Kecepatan Putaran Mata Pisau Akibat Speed droop pada Proses Pencacahan Ubi di PT. Hutahaean - Tarigan, Nurlianna; Tampubolon, Erick (CV. IRA PUBLISHING, 2024)
This research was conducted at PT. Hutahaean will analyze the causes of unstable blade rotational speed due to speed droop during the sweet potato chopping process at the cutting station. The cutting machine has eight blades to chop sweet potatoes into smaller pieces before further processing. Observations revealed several key factors causing the instability in blade speed, including electrical voltage fluctuations, wear on the drive motor, improper calibration, and debris buildup around machine components. The calculation results showed that the speed droop in blade rotation reached 5%, contributing to decreased production efficiency. Routine maintenance of machine components and adjustment of settings are recommended to address these issues.